Antimicrobial properties of alternative medicines used in the management of infections in diabetic patients: A comprehensive review - Elizabeth Bosede Aladejana; Olusesan Adeyemi Adelabu; Adebowale Emmanuel Aladejana; Sizwe Innocent Ndlovu (Elsevier, 2024)
Introduction: Diabetes mellitus poses major health risks due to increased vulnerability to infections stemming from weakened immune systems and physiological complications. With antimicrobial resistance worsening prognosis, diabetic infections affecting multiple body systems present critical treatment challenges. This review examines the antimicrobial properties of alternative medicines used in the management of diabetic infections and addresses the apparent research gap in this area. Method: A comprehensive literature search was conducted on databases (PubMed, Scopus, ScienceDirect, and Google Scholar) using specified keywords. Exclusion criteria removed non-relevant articles, resulting in the selection of articles published between 2012 and 2023, focusing on medicinal plants, polyherbal formulations, and antimicrobial effects against pathogens associated with diabetic infections. Results: The study revealed a significant research gap regarding the use of alternative medicines for diabetic infection treatment, as only 14 articles published between 2012 and 2023 were relevant to this review. Selected articles primarily addressed wound infections (39 %), diabetic foot ulcers (28 %), foot infections (17 %), urinary tract 11 %), and skin infections (5 %). Commonly used medicinal plants include Curcuma longa, Azadirachta indica, Zingiber officinale, and Glycyrrhiza glabra among others. The alternative medicines demonstrated significant antimicrobial potential against common microorganisms associated with diabetic infections, especially Gram-positive bacteria. Discussion: This review shows the potential of alternative medicines in the management of diabetic infections. This efficacy was attributed to diverse secondary metabolites present in medicinal plants, offering promising prospects for novel antimicrobial agents. Given the susceptibility of diabetic patients to microbial infections, further investigation into the efficacy of medicinal plants for the treatment of infections in diabetic patients is essential. Further research is also imperative to validate and standardize these therapies and conduct clinical trials to evaluate their safety and efficacy in diabetic infection management.